ECtHR: Verein KlimaSeniorinnen Schweiz and Others v. Switzerland (Application No. 53600/20, 9 April 2024) - Sandra Žatková; Petra Paľuchová (Bratislava Law Review, 2024)
The present paper focuses on the analysis of the landmark decision of the European Court of Human Rights in which the Court has, for the first time, ruled on human rights violation due to climate change. It begins with the description of the convention as a so-called living instrument that aims at the interpretation of the European Convention on Human Rights taking into account the current social circumstances and challenges, such as the growing need for environmental protection and addressing climate change. In the judgment in question, the Court held that Switzerland had violated the applicant's rights due to insufficient legislative measures to protect individuals from the adverse effects of climate change. As a result of the long-awaited but unconventional conclusion, the judgment has become the target of much criticism. The paper thus concentrates on the main seemingly innovative or rather surprising pillars of the judgment, such as the court's determination of locus standi, the scope of a state's positive obligations in the context of climate change and its related margin of appreciation, as well as the unprecedented consideration of scientific evidence. The paper concludes by summarising the possible implications of the court's arguments for similar future cases, which will undoubtedly increase in number.